Assessing Factors Influencing Moral Hazard of Mudharaba And Musyaraka Financing in Islamic Banking; Case Study in Surakarta - Indah Piliyanti; Afrilianti Afrilianti (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Unlike conventional banking, theoretically, Islamic banking has unique system called profit and loss sharing based financing which ensure both parties in the same level. But, in fact, some cases moral hazard has been occur in Islamic banking. Moral hazard is related to the circumstances, nature, and human characters that can increase the risk of large losses. Moral hazard in Islamic banking could occur in mudharaba and musyaraka financing when selecting, processing and monitoring of these mode of financing.The purpose of this study was to determine the factors lead to moral hazard in Islamic banking in Surakarta which offering mudharaba and musyaraka to their customers. This research was conducted at Islamic Banking in Surakarta, especially mudharabah and Musharaka financing as the unit of analysis. The data used in this study was obtained from the primary respondents to fill out questionnaires regarding to moral hazard issues. Factor analysis is used to determine the trend of the factors influencing moral hazard in profit sharing based financing. The results showed that the cause of the moral hazard of Muhdaraba and musyaraka financing is Asymmetric Information (0.917), client character (-0.884), scope of the contract (0.727), Monitoring (-0.881) and Collateral (0.647). The most dominant factor in the cause of moral hazard on mudharabah and Musharaka is Monitoring and Security.